Dominant Components of Technical Aspects in Identification of Football Athlete Talent Using AHP - Hafidz Nashrul Ghani; Rusdiana, Agus; Subarjah, Herman; Syahid, Angga M; Kurniawan, Tian (Halaman Olahraga Nusantara : Jurnal Ilmu Keolahragaan, 2024)
The aim of this research is to assess which technical aspects are dominant in identifying football athletes using the Analytic Hierarchy Process (AHP). This research uses a combination method. Mixed Methods Research (MMR) is a research approach that combines elements of qualitative and quantitative approaches in one Study. The sample used in this research consisted of 10 coaches in the sport of soccer, who had a national coaching license with more than 5 years of coaching experience in the sport of soccer. Data collection was carried out using a questionnaire distributed online via Google Form. From the results of this analysis, it is proven that passing has a very important role compared to other criteria. The order of priority scores obtained from this analysis is as follows: Passing = 0.420; Control = 0.253; Dribbling = 0.144; Shooting = 0.126; and Post = 0.057. The conclusion in this study is that passing has a higher percentage in the assessment. This shows that passing is the main factor in detecting the talent of soccer athletes.